Characterization and mechanism of phosphorus adsorption from wastewater by lanthanum calcium doped sludge/wheat straw biochar - Gong, Weijin; Tao, Chenhan; Tian, Zhenbang; Huang, Zuohua; Lin, Hongtao; Qi, Chaozhi; Yu, Zhengyang; Guo, Lina (Frontiers in Environmental Science, 2025)
The disposal of sludge and the treatment of phosphorus in water bodies are significant environmental challenges. This study explores the adsorption performance and mechanism of lanthanum-calcium modified sludge/wheat straw biochar (LC-SWBC). LC-SWBC was prepared through a one-step hydrothermal carbonization process and was used to remove phosphorus from water. The results indicate that La(OH)3 and Ca(OH)2 were successfully loaded onto the surface of the biochar. The adsorption of phosphates by LC-SWBC follows a pseudo-second-order kinetic model and the Langmuir model, with a maximum theoretical adsorption capacity of 80.78 mg P/g. LC-SWBC exhibits selective adsorption of phosphate under competitive anion experiments. In actual wastewater treatment, LC-SWBC can effectively remove phosphates, achieving a total phosphorus concentration of 0.77 mg/L at a dosage of 0.4 g/L, meet the discharge standard of class I B pollutants (1 mg/L) in GB 18918-2002 of China. In addition, the hydrothermal liquid of LC-SWBC is primarily composed of organic phosphorus (OP); after adsorption, the main component in the biochar LC-SWBC-P is apatite phosphate (AP), both of which provide biochemical utilization conditions for phosphorus resource recovery and recycling.